Investigating the involvement of kappa opioid receptor in mediating relapse related to morphine/methamphetamine (poly-drug) dependence using an immunohistochemistry technique - Nur Syafinaz binti Wasli (Kuliyyah of Pharmacy, International Islamic University Malaysia, 2018)
The upregulation of kappa opioid receptor (KOR) may results in dysphoria which could contribute to relapse towards various drugs of abuse. This research work is conducted to further investigate the involvement of KOR system in mediating relapse related to this poly-drug dependence at the brain level (striatum, amygdala, hippocampus, and prefrontal cortex). The reinstatement (relapse) model was initially developed for morphine (7.5 mg/kg), methamphetamine (1.0 mg/kg), and poly-drug (7.5 mg/kg and 1 mg/kg, respectively) using the conditioned place preference (CPP) paradigm. During reinstatement, a combination of 0.3 mg/kg buprenorphine and 1.0 mg/kg naltrexone (BUP/NTX) or saline was administered prior to the drug priming of morphine (2.5 mg/kg), methamphetamine (1.0 mg/kg), and poly-drug (2.5 mg/kg and 1 mg/kg, respectively). The change in KOR expression was quantitatively measured through the immunohistochemistry (IHC) technique by using the rabbit monoclonal antibody (EPR 18881) since it specifically binds at the KOR. Only the poly-drug group was investigated in order to evaluate the potential of this BUP/NTX treatment in IHC. The CPP results showed that the drug dependence models were successfully established in all groups, where the preference at the drug-paired compartment was significantly different (p < 0.001) compared to its baseline (23.45 ± 5.24 %, n = 10 vs. −8.55 ± 4.82 %, n = 12 [morphine]; 42.84 ± 6.83 %, n = 12 vs. −7.84 ± 4.31 %, n = 14 [methamphetamine]; and 34.91 ± 7.59 %, n = 10 vs. −11.16 ± 4.28 %, n = 13 [poly-drug]). During reinstatement, the BUP/NTX treatment successfully attenuated reinstatement to morphine (2.05 ± 11.04 %, n = 11 vs. −13.50 ± 5.18 %, n = 13, p > 0.05), but not for methamphetamine (35.03 ± 12.50 %, n = 10 vs. −6.75 ± 2.73 %, n = 14, p < 0.05). This treatment also successfully attenuated the reinstatement to poly-drug in the subgroup of mice that did not develop desensitisation behaviour (e.g., freezing behaviour), where the preference at the drug-paired compartment was not significantly different compared to its own baseline (19.14 ± 16.89 %, n = 5 vs. −16.14 ± 4.81 %, n = 12, p > 0.05). In IHC, only the striatum showed an increment in the KOR expression during reinstatement compared to post-conditioning in the saline group (33.390 ± 5.595 %, n = 12 vs. 16.730 ± 5.265 %, n = 12, p < 0.01). From the CPP results, it is suggested that the concomitant use of morphine and methamphetamine has triggered the opioid receptor system, which was not evidenced when methamphetamine alone was abused at low dose tested (1 mg/kg). Therefore, it is suggested that the KOR receptor system can be used as one of the targets to treat poly-drug dependence that involve opioid and methamphetamine.